2019
DOI: 10.1108/ihr-03-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

A recommended closed-loop assessment of learning outcomes process for hospitality programs

Abstract: Purpose Because of the increasingly higher expectations of accrediting organizations, calls for greater accountability from state governments and students’ demand for an education that prepares them for a career, most hospitality programs are now required to have an effective assessment of learning outcomes process. The increasing popularity of the assessment of learning outcomes process is viewed as highly positive because it can be considered as best-practices in higher education. The paper aims to discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…For the fifth step, rubrics were developed to provide standardisation for the measurement and evaluation of students' performance. This is in line with the study carried out by Reich et al (2019b) that suggested a fast and proper evaluation of students' performance can be used for OBE reporting. At this stage, coursework is selected over the final examination, as coursework can be used as a tool to measure knowledge, and assess problem-solving and other essential skills among students.…”
Section: Obe Implementation Processessupporting
confidence: 88%
See 4 more Smart Citations
“…For the fifth step, rubrics were developed to provide standardisation for the measurement and evaluation of students' performance. This is in line with the study carried out by Reich et al (2019b) that suggested a fast and proper evaluation of students' performance can be used for OBE reporting. At this stage, coursework is selected over the final examination, as coursework can be used as a tool to measure knowledge, and assess problem-solving and other essential skills among students.…”
Section: Obe Implementation Processessupporting
confidence: 88%
“…Students should be given different roles and assessments to enhance their learning experiences. Consequently, over-assessment of student learning can be avoided (Matthews & Mercer-Mapstone, 2018) as the assessments could be mapped to the intended learning outcomes through formative and summative assessment (Reich, Collins, DeFranco, & Pieper, 2019b).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations